One new species and a new record of Hoya (Apocynaceae, Asclepiadoideae) from Sulawesi, Indonesia - Ahmad, Roland Putra Pribadi; Zulfadli, Zulfadli; Rahayu, Sri; Rodda, Michele (Phytotaxa, 2021)
One new species of Hoya from Indonesia, Hoya batutikarensis, is described and illustrated. It is similar to H. camphorifolia but it has unusual corona lobes, each lobe has a spreading process at base and an apical triangular process, while the corona of H. camphorifolia has simple navicular lobes. Hoya ischnopus, a species so far only known to occur in New Guinea, is newly recorded in Sulawesi, considerably extending its distribution area.